Personalized epigenetics - Tollefsbol, Trygve O. (Translational epigenetics series., 2015)
Personalized Epigenetics discusses the core translatability of epigenetics to health management of individuals who have unique variations in their epigenetic signatures that can guide both disorder and disease prevention and therapy. The book details inter-individual variability in the major epigenetic process in humans consisting of DNA methylation, histone modifications, and noncoding RNA, and the diagnostic, prognostic, and therapeutic potential of the field, it also reviews the impact of the environment on epigenetic variations among individuals and the role of pharmacology and drug de.